School belonging, student bullying, and school disciplinary climate in TIMSS top-performance countries - Mohammadpour, Ebrahim (Universitas Papua, 2023)
There is insufficient research on how a student's sense of belonging at school affects their academic performance, particularly in the context of the five East Asian countries that consistently significantly outperform other nations in the Trends in International Mathematics and Science Study (TIMSS). This study examined the relationships between students' sense of school belonging, bullying, school climate, and mathematics achievement in Hong Kong, Japan, Korea, Singapore, and Taiwan. The data analyzed included mathematics test scores and questionnaire responses from 3265, 4446, 3861, 4853, and 4915 eighth graders from 136, 142, 168, 153, and 203 schools in these five countries, respectively. These students participated in TIMSS 2019 and the data was analyzed using path analysis technique. The results showed a significant relationship between a student's sense of belonging and achievement in all countries. However, this significant association disappeared for all countries except Korea and Singapore when factors such as bullying and school disciplinary climate were taken into account. The association was strongest among Singaporean students and weakest among Taiwanese students. The results of this study are consistent with previous research that attributes East Asian students' success to their cultural learning model rather than other factors. A sense of belonging at school is critical to promoting positive academic performance, development and well-being.